Pandemic Glissandi - Koutsomichalis, Marinos (My University, 2021)
‘Pandemic glissandi’ comes as a creative response to a period of sustained lockdowns and limited – if at all – opportunities for group physical/social activities and live music. A self-generative algorithm running on Anulios server produces four ever-modulated sine waves that slowly manoeuvre the stereophonic field and glide across a frequency continuum. Modulations are directed employing true random numbers – rather than the pseudo-random ones that are typically used in other algorithmic music scenaria – that are calculated from atmospheric noise and retrieved in real time.